Measurement of the top quark mass in the tt[bar] → dilepton channel from √ s = 8 TeV ATLAS data - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (Physics letters, 2016)
The top quark mass is measured in the tt¯→dilepton channel (lepton=e,μ) using ATLAS data recorded in the year 2012 at the LHC. The data were taken at a proton-proton centre-of-mass energy of s=8 TeV and correspond to an integrated luminosity of about 20.2 fb−1. Exploiting the template method, and using the distribution of invariant masses of lepton-b-jet pairs, the top quark mass is measured to be mtop=172.99±0.41 (stat)±0.74 (syst) GeV, with a total uncertainty of 0.84 GeV. Finally, a combination with previous ATLAS mtop measurements from s=7 TeV data in the tt¯→dilepton and tt¯→lepton+jets channels results in mtop=172.84±0.34 (stat)±0.61 (syst) GeV, with a total uncertainty of 0.70 GeV.
*The ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, V. Radescu, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2824 weitere Personen]
Im Titel steht der Buchstabe t mit einem Oberstrich
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 18.05.2020